Efficacy of different techniques for removal of calcium hydroxidechlorhexidine paste from root canals - Camargo, Carlos Henrique Ribeiro [UNESP]; Leal, Flávia Martins [UNESP]; Silva, Gleyce Oliveira [UNESP]; De Oliveira, Tatiana Rocha [UNESP]; Madureira, Paloma Grasso [UNESP]; Camargo, Samira Esteves Afonso (My University, 2016)
The purpose of this study was to evaluate the efficacy of different techniques for removal of combined calcium hydroxide [Ca(OH)2&] and chlorhexidine paste from root canals. Fifty single-rooted human teeth were prepared by oscillatory and rotary systems and filled with a paste of Ca(OH)2 and 2% chlorhexidine gel. After incubation for 14 days, the specimens were divided into 5 groups (n = 10), and the medication was removed by 1 of 5 different procedures. In group 1 (control), removal procedures involved a master apical file, foraminal debridement, and 5 mL of saline solution applied with the NaviTip irrigation needle. Group 2 was treated the same as group 1, but in addition 0.5 mL of 17% ethylenediaminetetraacetic acid was used for 3 minutes. In group 3, ultrasonic agitation was performed for 1 minute. Group 4 was treated as group 2, but the NaviTip FX needle was used for irrigation. In group 5, a master apical file, foraminal debridement, and 3-minute application of 5 mL of citric acid were used. After the root-cleaning procedures, the crowns were removed at the cementoenamel junction, and the roots were split longitudinally into halves. The success of intracanal medicament removal was observed under stereoscopic microscope and scanning electron microscope. Remnants of Ca(OH)2& were found in all experimental groups, regardless of the removal technique used. There was no statistically significant difference in cleanliness in the apical third of the root canal among groups 1, 2, and 3. Group 4 showed the best and group 5 the worst results with statistically significant differences. Overall, the NaviTip FX irrigation needle technique was more efficient in removing a Ca(OH)2-chlorhexidine paste from the root canal.
Keywords: Calcium hydroxide removal; Chlorhexidine; Citric acid; Ethylenediaminetetraacetic acid; Root canal; Ultrasonic agitation